RICIKAN KETHUK PADA KARAWITAN JAWA GAYA SURAKARTA - Joko Purwanto (Institut Seni Indonesia Surakarta, 2010)
To date, apart from being recognized as one of the structural instruments of the Javanese gamelan, the kethuk has rarely been a topic fordiscussion. It is as though its existence is no more than a supplementary instrument in a gamelan ageng ensemble. This article is a development of the works by Djojomlojo and Sunardi Wisnusubroto which discuss the function of the ricikan kethuk, or kethuk instrument in Surakarta style Javanese karawitan. This article attempts to discover the technique, function, and existence of the kethuk ina gamelan ageng ensemble. The ideas presented in this article are developed through a bibliographical study, observation, and interviews, together with a study of commercial cassette recordings and the writer's own private collection of recordings. The results of this study show that the kethuk can be played using three different patterns,namely limrah, salahan, and banggen. There are two techniques used for producing sound, which result in either a long or short sound. Pitch 2 (gulu) on the kethuk is ideal for all pathet in the slendro tuning, and pitch y (nem) is ideal for all pelog gending. The kethuk, with its own technique, supports the tempo set by the pamurba irama, or the instrument which controls the tempo, namely the kendang. In Surakarta style Javanesekarawitan, the kethuk is also important in connection with the title of a gending, in that it guides the other musicians in terms of their concept and patterns of treatment applied to the other instruments, in particular the kendang.Key words: kethuk, Djojomlojo and Sunardi, Surakarta Style Javanese Karawitan.